2020
DOI: 10.37934/arfmts.77.2.160175
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Energy and Exergy Analyses of a Roughened Solar Air Heater

Abstract: In this paper, eleven roughness elements in solar air heater duct analysed both energy and exergy were reviewed. Various roughness geometries such as ribs, twisted tap, baffles, and metal waste were surveyed about heat transfer and friction when the air flow is passing absorber plate. Evaluation criteria of roughness on the absorber plate including thermohydraulic performance parameter, thermal efficiency, effective efficiency, and exergy efficiency were presented and compared. Results showed that protruded ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Besides, solar energy is clean and safe, it can be captured anywhere and provide energy where other sources cannot. It makes the environment greener and cleaner [5].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, solar energy is clean and safe, it can be captured anywhere and provide energy where other sources cannot. It makes the environment greener and cleaner [5].…”
Section: Introductionmentioning
confidence: 99%
“…Applying solar technologies is one of the ways to facing global warming since they are causing no greenhouse gases emission [1,2]. Parabolic trough collector system (PTC) can be used to this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…The findings revealed that the suggested design had the greatest thermal efficiency, at 93 % as opposed to 70 % for standard solar air collectors. Phu and Luan [6] have reported on the properties of thermohydraulic and the effectiveness of the coarse geometry of solar air collector tubes.…”
Section: Introductionmentioning
confidence: 99%